Does ethnicity influence dementia, stroke and mortality risk? Evidence from the UK Biobank - Bonnechère, Bruno; Liu, Jun; Thompson, Alexander; Amin, Najaf; van Duijn, Cornelia (Frontiers in Public Health, 2023)
The number of people with dementia and stroke is increasing worldwide. There is increasing evidence that there are clinically relevant genetic differences across ethnicities. This study aims to quantify risk factors of dementia, stroke, and mortality in Asian and black participants compared to whites. 272,660 participants from the UKBiobank were included in the final analysis, among whom the vast majority are white (n = 266,671, 97.80%), followed by Asian (n = 3790, 1.35%), and black (n = 2358, 0.84%) participants. After adjusting for risk factors, black participants have an increased risk of dementia and stroke compared to white participants, while Asians has similar odds to the white. The risk of mortality is not different in blacks and white participants but Asians have a decreased risk. This study highlights the difference in the risk of dementia and stroke in black people living in the UK compared to white people.